Safety and efficacy of Avatec® 150G (lasalocid A sodium) as a feed additive for chickens for fattening and chickens reared for laying. (3rd August 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of Avatec ® 150G (lasalocid A sodium) for chickens for fattening and chickens reared for laying. In 2017, the FEEDAP Panel was not able to conclude on a safe dose for chickens for fattening and chickens reared for laying and no conclusion could be drawn on the anticoccidial efficacy of the additive at the lowest proposed used level (75 mg lasalocid A sodium/kg feed) in these species. In the present assessment, the applicant submitted new tolerance and efficacy studies in chickens for fattening to address the concerns identified by the FEEDAP Panel in its former opinion. In addition, the applicant proposed to decrease the maximum of the dose range from 125 to 100 mg lasalocid A sodium/kg complete feed. Based on the additional information, the FEEDAP Panel concludes that no safe level of lasalocid A sodium from Avatec ® 150G in feed for chickens for fattening can be identified. The FEEDAP Panel is not in the position to conclude on the coccidiostatic efficacy of Avatec ® 150G for chickens for fattening at the lowest proposed dose level of 75 mg lasalocid A sodium/kg complete feed due to the insufficient number of studies with positive results. The conclusions are extended to chickens reared for laying.